(3EJLGgGJ eYGUQI aj EOGQI GdeYQaI (B/s - (3GdRjGOGJ, eMeO YhGO GMeOs ((3YeGf(B: s (3OGQ UaGA ddfTQ h GdJhRjY(B, s, 2008)
(3GdeYQaI Gdeaghe GdNUGFU GdCfhGY, GOGQI GdeYQaI, YedjGJ GOGQI GdeYQaI hbjGSgG, feGPL GOGQI GdeYQaI, GSJQGJjLjGJ GOGQI GdeYQaI, GdeYdheGJ, fXe GdeYdheGJ hGOGQI GdeYQaI, GdGbJUGO GdeYQaj, GOGQI GdeYQaI hQCS GdeGd GdacQj, bjGS hJbhje GfJGLjI GdYed GdeYQaj, fTQ GdeYQaI hGdedcjI GdacQjI, GOGQI GdeYQaI hGdGHOGY GdJfXjej, OQGSGJ JWHjbjI aj GOGQI GdeYQaIs
Keywords: (3GOGQI GdGYeGds; (3GdJRhjOs; (3GdeYQaIs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s